Value Chain Development of Mamberamo Rice in Oe-Cusse-Timor Leste for Economic Sustainability - dos Santos, Joni Maria; Soewignyo, Tonny Irianto (Daengku: Journal of Humanities and Social Sciences Innovation, 2024)
Mamberamo rice value chain development towards economic sustainability in Oé-cusse Timor Leste. The research used descriptive and qualitative methods with a structured interview approach based on the prepared questionnaire. Main target of the research is rice farmers who have access to the agricultural land with a sample taken of 45 people. The sampling method randomly selected from 4 agricultural areas in Pante Makassar such as Costa, Lalicuk, Cunha and Lifau in which 5 representatives/ 100 ha selected for each area. The purpose of this research is to find out: (1) What are the current problems faced by the farmer related to the technologies and adoption of technologies to increase production? (2) What are the current problems faced by the farmer related to the storage system, processing, and marketing of Memberamo rice? The results of the study found that 36% of farmers answered that the problem they often faced was a lack of knowledge of technology to increase rice production, and 100% of farmers used inorganic fertilizers however 91% said it was very expensive. According to the result, after harvest, 98% of farmers prefer to store it at home, without temperature settings. In the Market Access variable, it was found that 87% of farmers found it difficult to bring their products to both local and national markets. Meanwhile, 56% of farmers answered that it was very difficult to access the market. Another finding is about the way they sell their products to the market – 78% of respondents sold their products without proper packaging. Keywords: Economic Sustainability, Mamberamo Rice, Market Access, Value Chain